Imaging Features of Triple Negative Breast Cancers : Mammography, Ultrasound and Magnetic Resonance Imaging = Značajke snimki trostruko negativnih karcinoma dojke : mamografija, ultrazvuk i magnetska rezonancija - Ivanac, Gordana (Array, 2021)
Breast cancer (BC) is a highly heterogeneous disease. Aim was to evaluate imaging features of triple negative breast cancers (TNBC) in comparison to non-TNBC. We reviewed data of 30 patients who had been diagnosed as having TNBC and 37 patients with non-TNBC (control group) using criteria described for mammography (MMG), ultrasound (US) and magnetic resonance imaging (MRI) in Breast Imaging-Reporting and Data System (BI-RADS) lexicon for image interpretation. Age of patients, size of tumor, multifocality, histological type, tumor grade and status of lymph nodes were reviewed. TNBC were more often histological grade 3 and had significantly more positive lymph nodes at the time of diagnosis on pathology reports. On MMG, US and MRI TNBC mostly appeared as regularly shaped masses. On US as hypoechogenic masses with no posterior acoustic features and on MRI as masses with rim type of enhancement, fast wash-in and plateau type of curves. Most frequent category reported after MMG and US was BI RADS 4, and after MRI BI RADS 5. In conclusion, our study confirmed higher histological grade of TNBC, as well as more frequent lymph node involvement in comparation to the non-TNBC. TNBC showed tendency to affect younger women and to be larger than non-TNBC. Although, they most often presented as a mass on mammography and sonography, in a significant number of cases they remained miscategorized, due to the benign imaging features. All cases are recognized on MRI where they appear as rim enhancing masses.